2015
DOI: 10.1177/0887403415589630
|View full text |Cite
|
Sign up to set email alerts
|

Examining Correctional Officers’ Fear of Victimization by Inmates: The Influence of Fear Facilitators and Fear Inhibitors

Abstract: Perceptions of fear in the correctional literature typically seek to predict factors such as procedural justice, turnover, and satisfaction rather than identify the antecedents to fear. In addition, studies on perceptions of safety consistently uncover female officers reporting higher levels of fear. The current study applies the concepts of fear facilitators and inhibitors, found in the general fear of crime literature, as a mechanism to explain perceptions of emotional and cognitive fear among correctional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 96 publications
(109 reference statements)
1
30
0
1
Order By: Relevance
“…The latter suggests that once workplace factors are taken into account, personal characteristics do not play as great a role in predicting perceived risk of danger on the job. The present study revealed higher perceptions of danger among nonWhites, which is consistent with prior research examining perception of fear of victimization (see Gordon & Baker, 2015;Gordon et al, 2013;Stichman & Gordon, 2015;Taxman & Gordon, 2009). This held only for the entire sample of correctional staff; the race variable was not significant for the subset of custody officers or among non-custody staff, but it did come close to statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The latter suggests that once workplace factors are taken into account, personal characteristics do not play as great a role in predicting perceived risk of danger on the job. The present study revealed higher perceptions of danger among nonWhites, which is consistent with prior research examining perception of fear of victimization (see Gordon & Baker, 2015;Gordon et al, 2013;Stichman & Gordon, 2015;Taxman & Gordon, 2009). This held only for the entire sample of correctional staff; the race variable was not significant for the subset of custody officers or among non-custody staff, but it did come close to statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…The impact of such relationships on the daily work environment, retention of correctional staff, and the climate and culture of the institutional environment is commonly investigated (Cullen et al, 1985; Dowden & Tellier, 2004; Griffin, 2001; Lambert, Cluse-Tolar, & Hogan, 2007; Lambert, Hogan, & Barton, 2002; Stichman & Gordon, 2015; Taxman & Gordon, 2009). Understanding the correlates of correctional staff perceptions on the dimension of workplace well-being or possible victimization by inmates is emerging in the literature (Gordon & Baker, 2015; Gordon et al, 2003; Gordon et al, 2013; Lai et al, 2012; Stichman & Gordon, 2015; Taxman & Gordon, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The crowdedness of the prison setting, its noises, and its typical odors (Crewe, 2011; Haney, 2006), as well as the frequent emotional encounters with inmates, bring the new officers into an unfamiliar, frightening, and threatening reality that requires rapid adjustment and specific modes of action (Gordon & Baker, 2015). Although various studies have revealed a link (causal or correlative) between the prison environment and high levels of mental and emotional distress (i.e., depression, loneliness, anxiety, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, como las mujeres son una parte considerable de la fuerza de trabajo, es importante revelar si hay alguna diferencia entre los oficiales de sexo femenino y masculino cuando se trata de estrés laboral. Pocos estudios han explorado disparadores de estrés laboral en oficiales penitenciarios (Campbell & Henderson, 2016;Finney et al, 2013;Gordon & Baker, 2015;Misis et al, 2013;Steiner & Wooldredge, 2015;Tenibiaje, 2013), y no se ha podido encontrar ningún estudio previo que haya examinado a oficiales en Costa Rica para ese propósito. Por lo tanto, el propósito de este estudio es establecer si una muestra de oficiales penitenciarios en Costa Rica presenta estrés laboral e identificar qué factores están relacionados con su presencia.…”
unclassified